2019
DOI: 10.3390/polym11121972
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Immunomodulatory Activity of a Novel Acid Polysaccharide from Solanum muricatum

Abstract: To investigate the structure and immunomodulatory activity of polysaccharide from Solanum muricatum, a novel acid polysaccharide named SMP-3a was purified from Solanum muricatum pulp through DEAE-52 cellulose column and Sephadex G-200 chromatography. Monosaccharide composition analysis showed that SMP-3a was mainly composed of rhamnose, arabinose, galactose, and galacturonic acid with the molar ratio of 1.09:2.64:1.54:1. The average molecular weight was found to be 227 kDa by high performance gel permeation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The pepino fruit is usually eaten as fresh juicy fruit, although some cultivars are used in vegetable salads due to their higher acidity content and herbaceous flavour (Prohens et al, 2002). Different studies found that pepino displays antioxidant, antidiabetic, anti-inflammatory and antitumor properties (Hsu et al, 2011;Shathish and Guruvayoorappan, 2014;Sudha et al, 2011;Virani et al, 2020;Wang et al, 2019;Yue et al, 2019Yue et al, , 2020. One of the most interesting features of pepino is its close phylogenetic relationship with the major crops potato and tomato (Särkinen et al, 2013;Spooner et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The pepino fruit is usually eaten as fresh juicy fruit, although some cultivars are used in vegetable salads due to their higher acidity content and herbaceous flavour (Prohens et al, 2002). Different studies found that pepino displays antioxidant, antidiabetic, anti-inflammatory and antitumor properties (Hsu et al, 2011;Shathish and Guruvayoorappan, 2014;Sudha et al, 2011;Virani et al, 2020;Wang et al, 2019;Yue et al, 2019Yue et al, , 2020. One of the most interesting features of pepino is its close phylogenetic relationship with the major crops potato and tomato (Särkinen et al, 2013;Spooner et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Among the salt-eluted polysaccharides, such as galactans, glucans, galacturonans, galacturonans have attracted more attention in modern pharmacology [5][6][7]. It is one kind of polysaccharides with a backbone of galactopyranouronic (GalpAc) residues and mostly distributed in plants as heterozygotes, which have extensively gained concerns because of their multiple biological properties, especially the immunomodulatory activities [8][9][10][11][12]. Studies have shown that these galacturonans derived from different plants (such as sweet cherry, stem lettuce, Gynostemma pentaphyllum tea, and elderflowers) with different molecular weights (9~2490 kDa) and different percentages of galacturonic acid (17.4%-77.18%) exhibited various immunoregulatory effects on macrophages by enhancing production of NO and cytokines at the minimum effective concentration (0.8~100 µg/mL).…”
Section: Introductionmentioning
confidence: 99%